Math, asked by pushpasapkota908, 11 months ago

find the sum to n terms of the series whose n terms is 3n^2+4n-2.

Answers

Answered by amankumaraman11
1

 \huge \bf{S  =   \frac{n(n +  1)}{2}} \\  \\   \sf  > S =  \frac{ {3n}^{2}  + 4n - 2( {3n}^{2}  + 4n - 2 + 1)}{2}   \\ \\   \tiny{  >  \sf S =  \frac{{3n}^{2}  + 4n - 2({3n}^{2}  + 4n - 1)}{2}}  \\  \\     \sf  \tiny{ > S =  \frac{[ {3n}^{2}({3n}^{2}  + 4n - 1) + 4n({3n}^{2}  + 4n - 1)  - 2({3n}^{2}  + 4n - 1)]}{2}}  \\  \\  \tiny{\sf  > S =   \frac{ {9n}^{4} +  {12n}^{3} -  {3n}^{2}   +  {12n}^{3} +   {16n}^{2} - 4n -  {6n}^{2}   - 8n + 2 }{2} } \\  \\  \tiny{ \sf >S =   \frac{ {9n}^{4} +  {24n}^{3}   +  {7n}^{2} - 12n + 2 }{2} } \\  \\  \tiny{ \sf >S = \frac{ \cancel2( {4.5n}^{4} +  {12n}^{3}  + 3.5 {n}^{2}  - 6n + 1 )}{ \cancel2}   } \\

Hence⤵

Required Sum is \tt{{4.5n}^{4} +  {12n}^{3}  + 3.5 {n}^{2}  - 6n + 1}.

Similar questions